Dieulafoy’s disease of the bronchial tree: a case report - Wadji, Massoud Baghai; Farahzadi, Athena (São Paulo Medical Journal, 2017)
CONTEXT: Dieulafoy’s disease of the bronchial tree is a very rare condition. Few cases have been reported in the literature. It can be asymptomatic or manifest with massive hemoptysis. This disease should be considered among heavy smokers when recurrent massive hemoptysis is present amid otherwise normal findings. The treatment can be arterial embolization or surgical intervention. CASE REPORT: A 16-year-old girl was admitted to the emergency department due to hemoptysis with an unknown lesion in the bronchi. She had suffered massive hemoptysis and respiratory failure one week before admission. Fiberoptic bronchoscopy revealed a lesion in the bronchus of the right lower lobe, which was suspected to be a Dieulafoy lesion. Segmentectomy of the right lower lobe and excision of the lesion was carried out. The outcome for this patient was excellent. CONCLUSION: Dieulafoy’s disease is a rare vascular anomaly and it is extremely rare in the bronchial tree. In bronchial Dieulafoy’s disease, selective embolization has been suggested as a method for cessation of bleeding. Nevertheless, standard anatomical lung resection is a safe and curative alternative.